The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/230949900801600123
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Rhinosporidiosis Destroying the Talus: A Case Report

Abstract: Rhinosporidiosis is a chronic granulomatous fungal disease caused by Rhinosporidiosis seeberi. It usually affects the mucocutaneous tissue of the nose; bone involvement is rare. We report the clinical features, diagnosis, and management of rhinosporidiosis involving the face, forehead, and right foot. As antimicrobial therapy was ineffective, a below-knee amputation was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Like the previously published data on gender predilection in rhinosporidiosis [5,8,[10][11][12][13], this study has also found a male predominance. This is apparently because menfolk remain primarily engaged in outdoor activities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Like the previously published data on gender predilection in rhinosporidiosis [5,8,[10][11][12][13], this study has also found a male predominance. This is apparently because menfolk remain primarily engaged in outdoor activities.…”
Section: Discussionsupporting
confidence: 85%
“…The practice of pond-bathing is considered a potential reason for the prevalence of the disease in rural population [1]. This also explains the predilection of involvement of accessible mucosal sites, most commonly the nose and nasopharynx, where the organism gains access through traumatized epithelium [5]. Over 70 % of the reported cases were in the nasal mucosa and about 15 % in the eye [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bony involvement is rare. Isolated osteolytic lesions have been reported involving the talus,7 tibia,89 femoral condyle,210 hand and feet,11 calcaneum,12 and clavicle 13. Dissemination to anatomically unrelated sites is mainly attributed to hematogenous spread 5.…”
Section: Discussionmentioning
confidence: 99%
“…[4,8,14] In cases of bone involvement three clinical settings can occur: (a) bone involvement with presence of mucocutaneous lesion as nasal polyp, (b) as a part of disseminated rhinosporidiosis, and (c) only primary bony lesion without any other organ involvement, [8] as in our case.…”
mentioning
confidence: 85%